Assessment of biochemical changes in Spinach (Spinacea oleracea L.) subjected to varying water regimes - Jabeen, Munifa; Akram, Nudrat Aisha; Muhammad Ashraf,; Aziz, Aniqa (Penerbit Universiti Kebangsaan Malaysia, 2019)
It is known that leafy vegetables including spinach (Spinacea oleracea L.) contain relatively high amount of water, therefore, their water requirement during the life cycle is comparatively more than the other vegetables. In addition, there is an association between osmoprotection and antioxidants with reference to drought stress tolerance. Keeping in mind these facts, the present study was conducted to assess the changes in plant growth, osmoprotectants, chlorophyll pigments and activities/levels of antioxidative system in spinach (Spinacea oleracea L.) grown under varying water deficit regimes with 40%, 60%, 80% and 100% field capacity (FC). Imposition of varying water regimes significantly decreased shoot and root fresh and dry weights, shoot plus root lengths, and chlorophyll b contents of spinach plants. Increase in proline, glycinebetaine (GB), total phenolics, ascorbic acid and malondialdehyde (MDA) contents as well as the activities of antioxidant enzymes including superoxide dismutase, peroxidase and catalase were observed in the spinach plants particularly at 40% FC. The most effective level of water stress for elevating the proline, GB and antioxidant levels/activities was observed at 40% FC followed by 60% FC. Hence, the results of this study suggested that upregulation of antioxidants and osmoprotectants is positively associated with the drought tolerance of spinach which depends on the severity of water stress level. These results can be used to narrow the gap between selection of plant species and requirement of irrigated water for the crops grown on dry land areas.